Magnesium-zirconium-titanium alloy, preparation method thereof and magnesium alloy product

By pretreating zirconium-containing and titanium-containing raw materials and performing second smelting and stirring in the melt of magnesium alloy, the problem of difficulty in uniform distribution of titanium and zirconium in magnesium alloy is solved, and the efficiency of magnesium-zirconium-titanium alloy is achieved Preparation and performance improvement.

CN119433256APending Publication Date: 2025-02-14HUNAN RARE EARTH METAL MATERIAL RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411599731.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively add titanium and zirconium to magnesium alloys simultaneously, resulting in increased production costs and limited application of magnesium-zirconium alloys.

Method used

通过对含锆原料和含钛原料进行预处理,去除表面氧化层,并在特定的熔体温度下与金属镁液混合,进行第二熔炼和第二搅拌,确保钛和锆均匀分布在镁基体 middle.

Benefits of technology

The particles of magnesium zirconium titanium alloy are small and the components are uniformly distributed, which reduces the production cost of the alloy and improves the performance of its application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433256A_ABST
    Figure CN119433256A_ABST
Patent Text Reader

Abstract

The invention provides a magnesium-zirconium-titanium alloy, a preparation method thereof and a magnesium alloy product. The preparation method comprises the following steps: respectively pretreating a zirconium-containing raw material and a titanium-containing raw material to obtain a pretreated zirconium-containing raw material and a pretreated titanium-containing raw material; melting metal magnesium to obtain metal magnesium liquid; mixing the metal magnesium liquid, the pretreated zirconium-containing raw material and the pretreated titanium-containing raw material to obtain a mixture; the mixture is subjected to second smelting and second stirring at the temperature of 660-800 DEG C, and the magnesium-zirconium-titanium alloy is obtained through casting; wherein the second stirring mode comprises one or more of mechanical stirring and electromagnetic stirring; the stirring power of electromagnetic stirring ranges from 50 kW to 85 kW, and the stirring frequency ranges from 90 Hz to 300 Hz; the mechanical stirring speed is 510 r / min to 650 r / min. Alloy particles in the magnesium-zirconium-titanium alloy prepared by the method are fine and are uniformly distributed, and the magnesium-zirconium-titanium alloy has excellent structure properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of alloy materials, and in particular to a magnesium-zirconium-titanium alloy and a preparation method thereof, and a magnesium alloy product. Background Art

[0002] Due to its low density, good damping and vibration reduction, thermal conductivity, electromagnetic shielding, and easy recycling and reproduction, magnesium alloys have broad application prospects in the fields of aviation, aerospace, automobiles, electronics, etc. However, magnesium alloys also have disadvantages such as low strength, low plasticity, high production cost, corrosion resistance, and low yield, which limit the further development and application of magnesium alloys.

[0003] Adding an appropriate amount of alloying elements to magnesium alloys can refine the grains, thereby increasing the strength of magnesium alloys and improving their processing properties. Zirconium (Zr) has an excellent effect on inhibiting grain growth, and has the same close-packed hexagonal structure as magnesium, with similar lattice constants; however, there are the following problems in practical applications: due to the large difference in density between zirconium and magnesium, the zirconium particles in the prepared magnesium-zirconium product are coarse, making the zirconium particles in the melt easy to settle, with low content and low yield; thus, the production cost of magnesium-zirconium alloys is increased, and its application is limited. Titanium (Ti) also has an excellent effect on inhibiting grain growth, and the crystal structures of titanium and magnesium are both close-packed hexagonal structures with similar lattice constants (lattice constants of titanium a=0.295nm, c=0.468nm; lattice constants of magnesium a=0.321nm, c=0.521nm), so titanium can become a heterogeneous core of magnesium; however, the melting point and density of titanium and magnesium are quite different, and the degree of alloying is low, making it difficult to effectively add titanium to magnesium.

[0004] Therefore, the preparation method of titanium-containing magnesium alloys still needs to be improved. Summary of the invention

[0005] Based on this, one or more embodiments of the present application provide a magnesium-zirconium-titanium alloy with fine particles and uniform component distribution, a preparation method thereof, and a magnesium alloy product.

[0006] According to a first aspect of an embodiment of the present application, a method for preparing a magnesium-zirconium-titanium alloy is provided, comprising the following steps:

[0007] Pre-treating the zirconium-containing raw material and the titanium-containing raw material to remove the surface oxide layer, respectively, to obtain a pre-treated zirconium-containing raw material and a pre-treated titanium-containing raw material;

[0008] Melting the metal magnesium to obtain metal magnesium liquid;

[0009] Mixing the metallic magnesium liquid, the pretreated zirconium-containing raw material and the pretreated titanium-containing raw material to obtain a mixture;

[0010] The mixture is subjected to a second melting and a second stirring at 660° C. to 800° C., and cast to obtain a magnesium-zirconium-titanium alloy;

[0011] Among them, the second stirring method includes one or more of mechanical stirring and electromagnetic stirring; the stirring power of the electromagnetic stirring in the second stirring is 50kW~85kW, and the stirring frequency is 90Hz~300Hz; the speed of the mechanical stirring in the second stirring is 510r / min~650r / min.

[0012] In one embodiment, the zirconium-containing raw material includes one or more of zirconium chips, zirconium sponge, zirconium powder and zirconium particles; the diameter of the zirconium sponge is 1 mm to 10 cm, the particle size of the zirconium powder is 100 μm to 800 μm, and the particle size of the zirconium particles is 1 mm to 50 mm.

[0013] In one embodiment, the titanium-containing raw material includes one or more of titanium powder, titanium particles, and sponge titanium; the particle size of the titanium powder is 3 μm~500 μm, the particle size of the titanium particles is 1 mm~3 mm, and the diameter of the sponge titanium is 1 mm~30 mm.

[0014] In one embodiment, the preparation method satisfies at least one of the following characteristics:

[0015] (1) The oxygen content on the surface of the pretreated zirconium-containing raw material is ≤0.03wt%;

[0016] (2) The oxygen content on the surface of the pretreated titanium-containing raw material is ≤0.03wt%;

[0017] (3) The density of the zirconium-containing raw material is 5.0 g / cm 3 ~6.5g / cm 3 ;

[0018] (4) The density of the titanium-containing raw material is 3.1 g / cm 3 ~4.5g / cm 3 .

[0019] In one of the embodiments, the mass ratio of the magnesium metal, the pretreated zirconium-containing raw material and the pretreated titanium-containing raw material is (60-90):(5-30):(3-10).

[0020] In one embodiment, the preparation method satisfies at least one of the following characteristics:

[0021] (1) the mixing step comprises: adding the pretreated zirconium-containing raw material and the pretreated titanium-containing raw material into the metal magnesium liquid at the same time; and the stirring power of the electromagnetic stirring in the second stirring is 55 kW to 85 kW, the stirring frequency is 180 Hz to 300 Hz, and the speed of the mechanical stirring in the second stirring is 550 r / min to 650 r / min;

[0022] (2) the mixing step comprises: mixing the zirconium-containing raw material and the metallic magnesium liquid, performing a first smelting and a first stirring to obtain a premixture; mixing the premixture with the titanium-containing raw material to obtain a mixture;

[0023] The temperature of the first smelting is 660°C to 800°C, and the time of the first smelting is 0.5h to 1h. The first stirring method is electromagnetic stirring or mechanical stirring. The stirring power of the electromagnetic stirring in the first stirring is 50kW to 75kW, the stirring frequency is 90Hz to 220Hz, and the speed of the mechanical stirring in the first stirring is 510r / min to 580r / min.

[0024] (3) the mixing step comprises: mixing the titanium-containing raw material and the metallic magnesium liquid, performing a first smelting and a first stirring to obtain a premixture; mixing the premixture with the zirconium-containing raw material to obtain a mixture;

[0025] The temperature of the first smelting is 660°C~800°C, and the time of the first smelting is 1h~3h; the first stirring method is electromagnetic stirring or mechanical stirring, and the electromagnetic stirring power in the first stirring is 60kW~85kW, and the electromagnetic stirring frequency is 120Hz~300Hz; the speed of mechanical stirring in the first stirring is 510r / min~600r / min.

[0026] In one embodiment, the preparation method satisfies at least one of the following characteristics:

[0027] (1) The total time of the first smelting and the second smelting is 1.5h~5h, and the time of the second smelting is 1.5h~4h;

[0028] (2) Melting is carried out in a protective atmosphere, wherein the protective gas in the protective atmosphere includes one or more of argon, sulfur hexafluoride and carbon dioxide.

[0029] In one embodiment, the protective gas includes argon, sulfur hexafluoride and carbon dioxide, and the volume ratio of the argon, the sulfur hexafluoride and the carbon dioxide is (0.1~2):(50~99):(30~99).

[0030] A magnesium-zirconium-titanium alloy is prepared by using the above-mentioned method for preparing the magnesium-zirconium-titanium alloy.

[0031] A magnesium alloy product, the raw materials for preparing the product include the magnesium-zirconium-titanium alloy.

[0032] Compared with the traditional technology, this application has the following beneficial effects:

[0033] The present application mixes the pretreated zirconium-containing raw material and titanium-containing raw material with the metal magnesium liquid, and stirs them at a specific melt temperature so that both titanium and zirconium can be melted into fine particles and evenly distributed in the magnesium matrix, thereby obtaining a magnesium-zirconium-titanium alloy with excellent structure. At the same time, adding a small amount of titanium to replace zirconium in the metal magnesium liquid can reduce the amount of zirconium used and reduce the cost of alloy preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0035] Figure 1 This is a schematic diagram of a stirring method of electromagnetic stirring in one embodiment of the present application;

[0036] Figure 2 This is a schematic diagram of a stirring method of electromagnetic stirring in one embodiment of the present application;

[0037] Figure 3 This is a 1500-fold microstructure diagram of the magnesium-zirconium-titanium alloy prepared in Example 1 of the present application;

[0038] Figure 4 This is a 10,000-fold microstructure diagram of the magnesium-zirconium-titanium alloy prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0039] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.

[0041] Magnesium and titanium have large differences in density, melting point, and boiling point. Currently, the methods for adding titanium to magnesium include: (1) Powder forming process: high-energy ball milling, discharge plasma sintering, heat treatment, and hot extrusion. The alloy prepared by this method is dense and has higher performance than the alloy prepared by casting; but the cost is high, the process is long, and the raw material is metal powder, which requires strict safety assurance. (2) Directly adding titanium powder, but the cost of titanium powder is high, and titanium powder is easily oxidized, inhaled, and deposited at the bottom of the melt during smelting, resulting in low yield; at the same time, the titanium particles in the magnesium alloy ingot are easy to agglomerate, introducing coarse TiO2 impurities, reducing the performance of the magnesium alloy.

[0042] The traditional preparation method of magnesium-zirconium master alloy is to reduce potassium zirconate with magnesium, using a large amount of alkali metal salt to cover the surface of the melt, with high reduction temperature, large amount of smoke and dust generated during the reduction process, large pollution, and serious corrosion to equipment; and the zirconium particles in the alloy are coarse, and some zirconium particles agglomerate into zirconium clusters larger than 10μm, resulting in serious component segregation, severe sedimentation during use, and low zirconium yield. Taking Mg-Zr30 prepared by magnesium thermal reduction as an example, the zirconium content of the upper layer of the ingot is less than 20wt%, and the zirconium content of the lower layer of the ingot is greater than 45wt%, with serious stratification.

[0043] In summary, there is currently no effective method to simultaneously add titanium and zirconium to magnesium alloys.

[0044] Based on this, some embodiments of the present application provide a method for preparing a magnesium-zirconium-titanium alloy, comprising steps S10 to S40.

[0045] Step S10: pretreating the zirconium-containing raw material and the titanium-containing raw material respectively to obtain a pretreated zirconium-containing raw material and a pretreated titanium-containing raw material;

[0046] Step S20: Melting the metal magnesium to obtain metal magnesium liquid;

[0047] Step S30: mixing the magnesium metal liquid, the pretreated zirconium-containing raw material and the pretreated titanium-containing raw material to obtain a mixture;

[0048] Step S40: performing a second melting and a second stirring on the mixture at 660° C. to 800° C., and casting to obtain a magnesium-zirconium-titanium alloy.

[0049] In the present application, the temperature of the second smelting is "660°C~800°C", which can be but is not limited to specific values ​​such as 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C or 800°C.

[0050] Zr and Ti are elements of the same family with similar chemical properties. Both can produce a good grain refining effect on magnesium. Adding Ti to Mg-Zr can reduce the cost of raw materials and alloy density. At the same time, effectively adding Ti to magnesium alloys can improve the grain refining effect of magnesium alloys.

[0051] Compared with Mg-Zr alloy and Mg-Ti alloy, under the same supercooling condition, both Zr and Ti can act as heterogeneous nucleation particles in Mg-Zr-Ti alloy, providing more heterogeneous nucleation particles for magnesium alloy, synergistically acting on the grain refinement of magnesium alloy, and the grain refinement effect is better than that of Mg-Zr or Mg-Ti alloy, which helps to improve the mechanical properties such as strength, toughness and plasticity of magnesium alloy. Based on the characteristics of Ti and Mg, Mg-Ti alloy is difficult to prepare, and Ti particles are easy to agglomerate in Mg. In Mg-Zr-Ti alloy, Ti and Zr are easier to combine, and Ti can combine with Zr to form fine dispersed particles distributed in the magnesium matrix. In some embodiments, the oxygen content of the surface of the pre-treated zirconium-containing raw material in step S10 is ≤0.03wt%.

[0052] In some embodiments, the oxygen content of the surface of the pretreated titanium-containing raw material in step S10 is ≤ 0.03 wt %.

[0053] In some specific examples, the pretreatment method includes grinding and polishing, pickling, sandblasting or electrolysis. It should be noted that the pretreatment method is not limited to the above, as long as it can reduce the oxygen content on the surface of the zirconium-containing raw material and the titanium-containing raw material.

[0054] In some embodiments, in step S20, the mass ratio of metallic magnesium, pretreated zirconium-containing raw material, and pretreated titanium-containing raw material is (60-90):(5-30):(3-10).

[0055] In some embodiments, the second stirring method in step S40 includes one or more of mechanical stirring and electromagnetic stirring.

[0056] In some specific examples, the stirring power of the electromagnetic stirring in step S40 is 50 kW to 85 kW, and the stirring frequency is 90 Hz to 300 Hz.

[0057] As an example, the stirring power of the electromagnetic stirring may be, but is not limited to, specific values ​​such as 50 kW, 55 kW, 60 kW, 65 kW, 70 kW, 75 kW, 80 kW or 85 kW. The frequency of the electromagnetic stirring may be, but is not limited to, 90 Hz, 100 Hz, 110 Hz, 120 Hz, 130 Hz, 140 Hz, 150 Hz, 160 Hz, 170 Hz, 180 Hz, 190 Hz, 200 Hz, 210 Hz, 220 Hz, 230 Hz, 240 Hz, 250 Hz, 260 Hz, 270 Hz, 280 Hz, 290 Hz or 300 Hz.

[0058] In some specific examples, the electromagnetic stirring in step S40 is biaxial electromagnetic stirring. It can be understood that biaxial electromagnetic stirring refers to applying electromagnetic forces in two different axial directions to make the stirred medium flow in two directions.

[0059] It can be understood that in step S40, the second stirring is performed simultaneously with the second smelting, so that titanium and zirconium will not settle and agglomerate.

[0060] In some specific examples, such as Figure 1 As shown, the magnetic field directions of the two electromagnetic induction fields in the biaxial electromagnetic stirring are the same.

[0061] In some specific examples, such as Figure 2 As shown, the magnetic field directions of the two electromagnetic induction fields in the biaxial electromagnetic stirring are opposite.

[0062] In some embodiments, the speed of mechanical stirring in step S40 is 510 r / min~650 r / min.

[0063] As an example, the speed of mechanical stirring can be but is not limited to specific values ​​such as 510r / min, 520r / min, 530r / min, 540r / min, 550r / min, 560r / min, 570r / min, 580r / min, 590r / min, 600r / min, 610r / min, 620r / min, 630r / min, 640r / min or 650r / min.

[0064] In some embodiments, the mixing step in step S30 includes step S31.

[0065] Step S31: adding the pretreated zirconium-containing raw material and the pretreated titanium-containing raw material into the metallic magnesium liquid at the same time to obtain a mixture.

[0066] It is understandable that when mixing is performed through step S31, the second stirring method in step S40 is electromagnetic stirring or mechanical stirring; the power of electromagnetic stirring is 55kW~85kW, the stirring frequency is 180Hz~300Hz, and the mechanical stirring speed is 550r / min~650r / min.

[0067] In some embodiments, the mixing step in step S30 includes step S32 and step S33.

[0068] Step S32: mixing the pretreated zirconium-containing raw material and the metallic magnesium liquid, and then performing a first smelting and a first stirring to obtain a premixture;

[0069] Step S33: mixing the premixture with the titanium-containing raw material to obtain a mixture.

[0070] In some specific examples, the first stirring method in step S32 is electromagnetic stirring or mechanical stirring; the electromagnetic stirring power is 50 kW to 75 kW, the frequency is 90 Hz to 220 Hz, and the mechanical stirring speed is 510 r / min to 580 r / min.

[0071] In some specific examples, the temperature of the first smelting in step S32 is 660° C. to 800° C. As an example, the temperature of the first smelting may be, but is not limited to, specific values ​​such as 660° C., 670° C., 680° C., 690° C., 700° C., 710° C., 720° C., 730° C., 740° C., 750° C., 760° C., 770° C., 780° C., 790° C. or 800° C.

[0072] In some specific examples, the time for the first smelting and the first stirring in step S32 is 0.5 h to 1 h. As an example, the time for the first smelting can be, but is not limited to, 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h or 1 h.

[0073] In some specific examples, in step S32, the first smelting is performed in a protective atmosphere, and the protective gas in the protective atmosphere includes one or more of argon, sulfur hexafluoride and carbon dioxide.

[0074] Understandably, by first adding the zirconium-containing raw material into the metallic magnesium liquid, a smaller stirring force can be used to dissolve the zirconium into small particles; thereafter, when the titanium-containing raw material is added, the zirconium that has been dissolved into small particles is not easy to wrap the titanium.

[0075] In some embodiments, the mixing step in step S30 includes step S34 and step S35.

[0076] Step S34: mixing the pretreated titanium-containing raw material and the magnesium liquid, and then performing a first smelting and a first stirring to obtain a premixture;

[0077] Step S35: mixing the premix with the zirconium-containing raw material to obtain a mixture.

[0078] In some specific examples, the temperature of the first smelting in step S34 is 660°C to 800°C.

[0079] In some specific examples, the time of the first smelting and the first stirring in step S34 is 1 hour to 3 hours. As an example, the time of the second smelting can be, but is not limited to, specific values ​​such as 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours.

[0080] In some specific examples, in step S34, the first smelting is performed in a protective atmosphere, and the protective gas in the protective atmosphere includes one or more of argon, sulfur hexafluoride and carbon dioxide.

[0081] In some specific examples, the first stirring method in step S34 is electromagnetic stirring or mechanical stirring. The power of the electromagnetic stirring in the first stirring is 60kW~85kW and the stirring frequency is 120Hz~300Hz; the speed of the mechanical stirring in the first stirring is 510r / min~600r / min.

[0082] Understandably, adding the titanium-containing raw material into the metallic magnesium liquid first can dissolve it into small particles first, thereby preventing the titanium from being wrapped by zirconium; however, a longer smelting time is required.

[0083] It can be understood that the above method for adding samples and stirring can fully integrate zirconium and titanium with the magnesium matrix without causing particle agglomeration and inability to disperse.

[0084] In some embodiments, the second smelting time in step S40 is 1.5 h to 4 h. As an example, the second smelting time can be, but is not limited to, specific values ​​such as 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h or 4 h.

[0085] In some specific examples, the total duration of the first smelting and the second smelting is 1.5 h to 5 h.

[0086] In some embodiments, the smelting is performed in a protective atmosphere in step S40, and the protective gas in the protective atmosphere includes one or more of argon, sulfur hexafluoride and carbon dioxide.

[0087] In some specific examples, the protective gas in step S40 includes argon, sulfur hexafluoride and carbon dioxide, and the volume ratio of argon, sulfur hexafluoride and carbon dioxide is (0.1~2):(50~99):(30~99).

[0088] In some embodiments, the zirconium-containing raw material includes one or more of zirconium chips, zirconium sponge, zirconium powder and zirconium particles.

[0089] In some embodiments, the density of the zirconium-containing raw material is 5.0 g / cm 3 ~6.5g / cm 3 As an example, the density of the zirconium-containing raw material may be, but is not limited to, 5.0 g / cm 3 , 5.1g / cm 3 , 5.2g / cm 3 , 5.3g / cm 3 , 5.4g / cm 3 , 5.5g / cm 3 , 5.6g / cm 3 , 5.7g / cm 3 , 5.8g / cm 3 , 5.9g / cm 3 、6.0g / cm 3 、6.1g / cm 3 、6.2g / cm 3 、6.3g / cm 3 、6.4g / cm 3 or 6.5g / cm 3 And other specific values.

[0090] In some optional examples, the density of the zirconium-containing raw material is 6.0 g / cm 3 ~6.35g / cm 3 .

[0091] In some specific examples, the diameter of the zirconium sponge is 1 mm to 10 cm. As an example, the diameter of the zirconium sponge can be but is not limited to 1 mm, 50 mm, 100 mm, 200 mm, 300 mm, 400 mm, 500 mm, 600 mm, 700 mm, 800 mm, 900 mm, 1 cm, 2 cm, 3 cm, 4 cm, 5 cm, 6 cm, 7 cm, 8 cm, 9 cm or 10 cm.

[0092] In some specific examples, the particle size of the zirconium powder is 100 μm to 800 μm; as an example, the particle size of the zirconium powder can be but is not limited to specific values ​​such as 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm or 800 μm.

[0093] In some specific examples, the particle size of the zirconium particles is 1 mm to 50 mm. As an example, the particle size of the zirconium particles can be but is not limited to 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 20 mm, 30 mm, 40 mm or 50 mm.

[0094] In some embodiments, the titanium-containing raw material includes one or more of titanium powder, titanium particles, and titanium sponge.

[0095] In some embodiments, the density of the titanium-containing raw material is 3.3 g / cm 3 ~4.5g / cm 3 As an example, the density of the titanium-containing raw material may be, but is not limited to, 3.3 g / cm 3 、3.4g / cm 3 , 3.5g / cm 3 、3.6g / cm 3 、3.7g / cm 3 、3.8g / cm 3 、3.9g / cm 3 , 4.0g / cm 3 , 4.1g / cm 3 , 4.2g / cm 3 , 4.3g / cm 3 4.4g / cm 3 or 4.5g / cm 3 And other specific values.

[0096] In some optional examples, the density of the titanium-containing raw material is 4.1 g / cm 3 ~4.5g / cm 3 .

[0097] In some specific examples, the particle size of the titanium powder is 3μm~500μm; as an example, the particle size of the titanium powder can be but not limited to 3μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 200μm, 300μm, 400μm or 500μm and other specific values.

[0098] In some specific examples, the particle size of the titanium particles is 1 mm to 3 mm. As an example, the particle size of the titanium particles can be but is not limited to 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2 mm or 3 mm.

[0099] In some specific examples, the diameter of the titanium sponge is 1 mm to 30 mm. As an example, the diameter of the titanium sponge can be, but is not limited to, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 20 mm or 30 mm.

[0100] It can be understood that the size and density of the zirconium-containing raw material and the titanium-containing raw material are controlled within the above-mentioned specific ranges so that titanium and zirconium can be melted quickly and efficiently into smaller pieces and evenly distributed in the melt.

[0101] The preparation method of the present application has at least the following advantages: (1) It has the advantages of simple process, no need for expensive equipment, environmental friendliness (no smoke and dust is generated during the preparation process), low energy consumption, and easy mass production. (2) No salt substances are required, and there is less corrosion damage to equipment and supporting facilities; the prepared magnesium zirconium titanium alloy has no molten salt inclusions, can be stored and transported for a long time, and does not deliquesce. (3) Adding an appropriate amount of Ti to replace part of Zr can effectively reduce the density and preparation cost of the alloy; and during the use of magnesium zirconium titanium alloy, the sedimentation rate of Ti in the magnesium melt is lower than that of Zr, which can improve the effective utilization rate of Ti. (4) The preparation process of magnesium titanium alloy is difficult. When titanium is introduced into magnesium zirconium alloy, titanium is more likely to combine with zirconium under certain conditions, and titanium can enter the magnesium alloy.

[0102] A magnesium-zirconium-titanium alloy is prepared by using the above-mentioned method for preparing the magnesium-zirconium-titanium alloy.

[0103] The magnesium-zirconium-titanium alloy prepared in the present application has the advantages of small crystal particles and low component segregation, and can meet the needs of different application fields.

[0104] A magnesium alloy product, the raw materials for preparing the product include the magnesium-zirconium-titanium alloy.

[0105] It is understandable that the raw materials for preparing the magnesium alloy product may also include other raw materials.

[0106] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.

[0107] Example 1

[0108] (1) Surface pretreatment was performed on zirconium chips and titanium powder to remove surface oxides. The oxygen content was tested using a nitrogen oxygen analyzer. The oxygen content of the pretreated zirconium chips was <0.012wt%, the length was 1cm~3cm, and the density was 6.32g / cm 3 ; The oxygen content of the pretreated titanium powder is <0.025wt%, the particle size is 350μm, and the density is 4.4g / cm 3 .

[0109] (2) Weighing a magnesium ingot, pretreated zirconium chips and pretreated titanium powder in a mass ratio of 67:25:8; putting the magnesium ingot into a smelting furnace for melting, and after the magnesium ingot is melted, adding the pretreated zirconium chips for a first smelting and a first stirring to obtain a premix; the temperature of the first smelting is 720°C; the protective gas during the first smelting process includes argon and sulfur hexafluoride in a volume ratio of 99:1; the first stirring method is electromagnetic stirring; the stirring power is 50 kW, the frequency is 90 Hz, and the melting and stirring time is 0.5 h.

[0110] (3) The pretreated titanium powder is then added to the premixture to obtain the mixture, and the second melting and second stirring are started. The temperature of the second melting is 740°C. During the second melting process, the protective gas includes argon and sulfur hexafluoride in a volume ratio of 99:1. The time of the second melting and the second stirring is 2 hours. The melt is then cast into a mold to obtain a magnesium-zirconium-titanium intermediate alloy.

[0111] The second stirring mode is electromagnetic stirring, the stirring power is 65 kW, the stirring frequency is 300 Hz, and the direction of electromagnetic stirring is biaxial co-directional electromagnetic stirring.

[0112] Figure 3 This is a 1500-fold microstructure diagram of the magnesium-zirconium-titanium master alloy prepared in this embodiment; Figure 4 This is a 10,000-fold microstructure diagram of the magnesium-zirconium-titanium master alloy prepared in this embodiment. Figure 3 and Figure 4 It can be seen that the magnesium-zirconium-titanium master alloy prepared in Example 1 has fine particles and is evenly distributed.

[0113] Example 2

[0114] (1) Surface pretreatment was performed on zirconium sponge and titanium sponge to remove surface oxides. The oxygen content was tested using a nitrogen oxygen analyzer. The oxygen content of the pretreated zirconium sponge was <0.012wt%, the diameter was 5cm~10cm, and the density was 6.01g / cm 3 The oxygen content of the pretreated titanium sponge powder is <0.012wt%, the diameter is 5mm, and the density is 4.32g / cm 3 .

[0115] (2) Weighing a magnesium ingot, pretreated zirconium sponge, and pretreated titanium sponge in a mass ratio of 89:6:5; placing the magnesium ingot into a smelting furnace for a second smelting and a second stirring; after the magnesium ingot is melted, adding the pretreated zirconium sponge and pretreated titanium sponge at the same time.

[0116] The temperature of the second smelting is 800°C. The protective gas in the second smelting process includes argon, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:48:2. The time of the second smelting and the second stirring is 3.5h. The melt is then cast into a mold to obtain a magnesium-zirconium-titanium intermediate alloy.

[0117] The second stirring method is mechanical stirring, and the stirring speed is 580r / min.

[0118] Example 3

[0119] (1) Surface pretreatment was performed on zirconium powder and titanium sponge to remove surface oxides. The oxygen content was tested using a nitrogen oxygen analyzer. The oxygen content of the pretreated zirconium powder was <0.018wt%, the particle size was 30μm~100μm, and the density was 6.3g / cm 3 ; The oxygen content of the pretreated titanium sponge is <0.018wt%, the diameter is 1mm~3mm, and the density is 4.13g / cm 3 .

[0120] (2) Weighing a magnesium ingot, pretreated zirconium powder and pretreated titanium sponge in a mass ratio of 79:18:3; putting the magnesium ingot into a smelting furnace for smelting, and after the magnesium ingot is melted, adding the pretreated titanium sponge for a first smelting and a first stirring to obtain a premix; the temperature of the first smelting is 700°C; the protective gas during the first smelting process includes argon, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:48:2; the first stirring method is electromagnetic stirring, with a power of 85 kW, a frequency of 300 Hz, and a stirring time of 3 h.

[0121] (3) Add the pretreated zirconium powder to the premixed mixture, and perform a second smelting and a second stirring on the obtained mixture. The temperature of the second smelting is 760°C, and the protective gas during the smelting process includes argon, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:48:2. The time of the second smelting and the second stirring is 2 hours; then the melt is cast into a mold to obtain a magnesium-zirconium-titanium master alloy.

[0122] The second stirring mode is electromagnetic stirring; the stirring power of the electromagnetic stirring is 75 kW, the stirring frequency is 130 Hz, the direction of the electromagnetic stirring in the first 1 h is biaxial co-directional electromagnetic stirring, and the direction of the electromagnetic stirring in the last 1 h is biaxial reverse electromagnetic stirring.

[0123] Example 4

[0124] (1) The zirconium sponge and titanium particles were pretreated to remove the surface oxides. The oxygen content was tested using a nitrogen oxygen meter. The oxygen content of the pretreated zirconium sponge was <0.045wt%, the diameter was 1mm~10mm, and the density was 5.6g / cm 3 The oxygen content of the pretreated titanium particles is less than 0.025wt%, the particle size is 2mm~3mm, and the density is 3.1g / cm 3 .

[0125] (2) Weighing a magnesium ingot, pretreated zirconium sponge, and pretreated titanium particles in a mass ratio of 60:30:10; placing the magnesium ingot into a smelting furnace for smelting; and after the magnesium ingot is melted, adding the pretreated zirconium sponge and pretreated titanium particles.

[0126] The temperature of the smelting furnace is 680°C. During the smelting process, the protective gas includes argon, carbon dioxide and sulfur hexafluoride in a volume ratio of 60:39:1, and the mixed smelting is carried out for 4 hours under the action of mechanical stirring; then the melt is cast into a mold to obtain a magnesium-zirconium-titanium intermediate alloy.

[0127] Among them, the speed of mechanical stirring is 650r / min.

[0128] Example 5

[0129] (1) Surface pretreatment was performed on zirconium particles and titanium powder to remove surface oxides. The oxygen content was tested using a nitrogen oxygen analyzer. The oxygen content of the pretreated zirconium particles was <0.029wt%, the length was 1mm~30mm, and the density was 6.33g / cm 3 ; The oxygen content of the pretreated titanium powder is <0.025wt%, the particle size is 30μm~100μm, and the density is 4.1g / cm 3 .

[0130] (2) Weighing a magnesium ingot, pretreated zirconium particles and pretreated titanium powder in a mass ratio of 60:30:10; putting the magnesium ingot into a smelting furnace for smelting, and after the magnesium ingot is melted, adding the pretreated titanium powder for a first smelting and a first stirring to obtain a premix; the temperature of the first smelting is 660°C; the protective gas during the first smelting process includes argon, carbon dioxide and sulfur hexafluoride in a volume ratio of 20:79.9:0.1; the first stirring method is electromagnetic stirring, with a power of 65 kW, a frequency of 220 Hz and a stirring time of 1 h.

[0131] (3) Add the pretreated zirconium powder to the premixed mixture, and perform a second smelting and a second stirring on the obtained mixture. The temperature of the second smelting is 660°C, and the protective gas during the second smelting process includes argon, carbon dioxide and sulfur hexafluoride in a volume ratio of 20:79.9:0.1. The time of the second smelting and the second stirring is 2 hours; then, the melt is cast into a mold to obtain a magnesium zirconium titanium master alloy.

[0132] The second stirring mode is electromagnetic stirring, the stirring power is 85 kW, the stirring frequency is 120 Hz, and the direction of electromagnetic stirring is biaxial co-directional electromagnetic stirring.

[0133] Comparative Example 1

[0134] (1) Weigh magnesium ingot, potassium fluorozirconate, potassium fluorotitanate and potassium chloride in a mass ratio of 1:1.4:0.8:2.2.

[0135] (2) The above materials are put into a smelting furnace for smelting, the temperature of the smelting furnace is set to 1150°C, and manual stirring is performed for 30 minutes. The melt in the smelting furnace is then cast into a mold to obtain a magnesium-zirconium-titanium intermediate alloy.

[0136] Comparative Example 2

[0137] The method is basically the same as Example 1, except that electromagnetic stirring is not performed during smelting.

[0138] Comparative Example 3

[0139] The method is basically the same as Example 1, except that the surface pretreatment of zirconium chips and titanium powder is not performed.

[0140] Comparative Example 4

[0141] It is basically the same as Example 1, except that the melting temperature is different. The melting temperature in Comparative Example 4 is 850°C.

[0142] Comparative Example 5

[0143] It is basically the same as Example 1, except that the power of the electromagnetic stirring is different. In Comparative Example 5, the stirring power of the electromagnetic stirring is 40 kW and the stirring frequency is 450 Hz.

[0144] The alloy content, impurity content and average particle size of the magnesium-zirconium-titanium alloys prepared in the above Examples 1 to 5 and Comparative Examples 1 to 5 were statistically analyzed, and the results are shown in Table 1.

[0145] Table 1

[0146]

[0147] Further, in order to analyze the composition segregation of the magnesium-zirconium-titanium alloys prepared in the above Examples 1 to 5 and Comparative Examples 1 to 5, the zirconium and titanium contents of the upper and lower layers of each magnesium-zirconium-titanium alloy were detected, and the degree of composition segregation was calculated as (maximum value - minimum value) / average value × 100%. The results are shown in Table 2.

[0148] Table 2

[0149]

[0150] As shown in Tables 1 and 2, Ti and Zr in the magnesium-zirconium-titanium alloy prepared by the method of the present application are fully dissolved into fine particles and evenly distributed in the magnesium matrix, so the crystal particle size of the magnesium-zirconium-titanium alloy prepared is small; at the same time, the component segregation rates of Ti and Zr in the magnesium-zirconium-titanium alloy prepared by the present application are both low. The above results show that the method of the present application has a good effect on the refinement of magnesium grains in magnesium alloys.

[0151] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0152] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a magnesium-zirconium-titanium alloy, characterized in that: The steps include: Pre-treating the zirconium-containing raw material and the titanium-containing raw material to remove the surface oxide layer, respectively, to obtain a pre-treated zirconium-containing raw material and a pre-treated titanium-containing raw material; Melting the metal magnesium to obtain metal magnesium liquid; Mixing the metallic magnesium liquid, the pretreated zirconium-containing raw material and the pretreated titanium-containing raw material to obtain a mixture; The mixture is subjected to a second melting and a second stirring at 660° C. to 800° C., and cast to obtain a magnesium-zirconium-titanium alloy; Among them, the second stirring method includes one or more of mechanical stirring and electromagnetic stirring; the stirring power of the electromagnetic stirring in the second stirring is 50kW~85kW, and the stirring frequency is 90Hz~300Hz; the speed of the mechanical stirring in the second stirring is 510r / min~650r / min.

2. The method for preparing magnesium-zirconium-titanium alloy according to claim 1, characterized in that: The zirconium-containing raw material includes one or more of zirconium chips, zirconium sponge, zirconium powder and zirconium particles; the diameter of the zirconium sponge is 1 mm to 10 cm, the particle size of the zirconium powder is 100 μm to 800 μm, and the particle size of the zirconium particles is 1 mm to 50 mm.

3. The method for preparing magnesium-zirconium-titanium alloy according to claim 1, characterized in that: The titanium-containing raw material includes one or more of titanium powder, titanium particles, and sponge titanium; the particle size of the titanium powder is 3μm~500μm, the particle size of the titanium particles is 1mm~3mm, and the diameter of the sponge titanium is 1mm~30mm.

4. The method for preparing magnesium-zirconium-titanium alloy according to claim 1, characterized in that: The preparation method meets at least one of the following characteristics: (1) The oxygen content on the surface of the pretreated zirconium-containing raw material is ≤0.03wt%; (2) The oxygen content on the surface of the pretreated titanium-containing raw material is ≤0.03wt%; (3) The density of the zirconium-containing raw material is 5.0 g / cm 3 ~6.5g / cm 3 ; (4) The density of the titanium-containing raw material is 3.0 g / cm 3 ~4.5g / cm 3 .

5. The method for preparing magnesium-zirconium-titanium alloy according to claim 1, characterized in that: The mass ratio of the magnesium metal, the pretreated zirconium-containing raw material and the pretreated titanium-containing raw material is (60-90):(5-30):(3-10).

6. The method for preparing magnesium-zirconium-titanium alloy according to claim 1, characterized in that: The preparation method meets at least one of the following characteristics: (1) The mixing step comprises: adding the pretreated zirconium-containing raw material and the pretreated titanium-containing raw material into the magnesium liquid at the same time; and the stirring power of the electromagnetic stirring in the second stirring is 55 kW to 85 kW, the stirring frequency is 180 Hz to 300 Hz, and the speed of the mechanical stirring in the second stirring is 550 r / min to 650 r / min; (2) The mixing step comprises: mixing the pretreated zirconium-containing raw material and the metal magnesium liquid, and then performing a first smelting and a first stirring to obtain a premixture; mixing the premixture with the titanium-containing raw material to obtain a mixture; The temperature of the first smelting is 660°C to 800°C, and the time of the first smelting is 0.5h to 1h. The first stirring method is electromagnetic stirring or mechanical stirring. The stirring power of the electromagnetic stirring in the first stirring is 50kW to 75kW, the stirring frequency is 90Hz to 220Hz, and the speed of the mechanical stirring in the first stirring is 510r / min to 580r / min. (3) The mixing step comprises: mixing the pretreated titanium-containing raw material and the metal magnesium liquid, and then performing a first smelting and a first stirring to obtain a premixture; mixing the premixture with the zirconium-containing raw material to obtain a mixture; The temperature of the first smelting is 660°C~800°C, and the time of the first smelting is 1h~3h; the first stirring method is electromagnetic stirring or mechanical stirring, the electromagnetic stirring power in the first stirring is 60kW~85kW, the electromagnetic stirring frequency is 120Hz~300Hz, and the mechanical stirring speed in the first stirring is 510r / min~600r / min.

7. The method for preparing a magnesium-zirconium-titanium alloy according to any one of claims 1 to 6, characterized in that: The preparation method meets at least one of the following characteristics: (1) The second smelting time is 1.5h~4h; (2) performing a second smelting in a protective atmosphere, wherein the protective gas in the protective atmosphere comprises one or more of argon, sulfur hexafluoride and carbon dioxide.

8. The method for preparing magnesium-zirconium-titanium alloy according to claim 7, characterized in that: The protective gas includes argon, sulfur hexafluoride and carbon dioxide, and the volume ratio of the argon, the sulfur hexafluoride and the carbon dioxide is (0.1~2):(50~99.9):(30~99.9).

9. A magnesium-zirconium-titanium alloy, characterized in that: The magnesium-zirconium-titanium alloy is prepared by the preparation method of any one of claims 1 to 8.

10. A magnesium alloy product, characterized in that: The raw materials for its preparation include the magnesium-zirconium-titanium alloy described in claim 9.